2020
DOI: 10.1186/s12935-020-01547-7
|View full text |Cite
|
Sign up to set email alerts
|

CircUBE2D2 (hsa_circ_0005728) promotes cell proliferation, metastasis and chemoresistance in triple-negative breast cancer by regulating miR-512-3p/CDCA3 axis

Abstract: Background Triple-negative breast cancer (TNBC) is a clinically aggressive subtype of breast cancer with a bad prognosis. Chemotherapy is still the standard of care for TNBC treatment. Circular RNAs (CircRNAs) have been recently discovered to be closely involved in the initiation and development of human cancers. Herein, we focus our attention on the functions and underlying mechanisms of circUBE2D2 in TNBC progression and chemoresistance. Methods The expression of circUBE2D2, miR-512-3p, and cell division c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 39 publications
0
60
0
Order By: Relevance
“…Many studies have elucidated the role of CDCA3 expression in diverse tumors; for instance, CDCA3 inhibits the formation of tumors by affecting cell growth and inducing apoptosis in pancreatic cancer [ 32 ]. CDCA3 expression affects other cancers as well, such as renal cell carcinoma [ 33 ], breast cancer [ 34 ], acute myeloid leukemia [ 35 ], and non-small-cell lung cancer [ 5 ]. Recently, some studies have suggested that CDCA3 is expressed differently between normal tissues and tumor tissues; however, only few studies have explained the underlying mechanism and pathways of CDCA3 expression in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have elucidated the role of CDCA3 expression in diverse tumors; for instance, CDCA3 inhibits the formation of tumors by affecting cell growth and inducing apoptosis in pancreatic cancer [ 32 ]. CDCA3 expression affects other cancers as well, such as renal cell carcinoma [ 33 ], breast cancer [ 34 ], acute myeloid leukemia [ 35 ], and non-small-cell lung cancer [ 5 ]. Recently, some studies have suggested that CDCA3 is expressed differently between normal tissues and tumor tissues; however, only few studies have explained the underlying mechanism and pathways of CDCA3 expression in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, circKIF4A and circITCH were proved to upregulate its parental genes via acting as sponges for miRNAs thereby mediating TNBC progress [ 51 , 52 ]. Additionally, more miRNA-sponge functions of circRNAs have been and are being validated in TNBC, including circUBAP2/miR-661/MTA1 [ 53 ], circPLK1/miR-296-5p/PLK1 [ 54 ], circTFCP2L1/miR-7/PAK1 [ 55 ], circAHNAK1/miR-421/RASA1 [ 56 ], circAGFG1/miR-195-5p/CCNE1 [ 57 ], circZEB1/miR-448/eEF2K [ 58 ], circGNB1/miR-141-5p/IGF1R [ 59 ], circRPPH1/miR-556-5p/YAP1 [ 60 ], circCDYL/miR-190a-3p/TP53INP1 [ 61 ], circEIF3M/miR-33a/cyclinD1 [ 62 ], circUBE2D2/miR-512-3p/CDCA3 [ 63 ], and circPGAP3/miR-330-3p/Myc [ 64 ].…”
Section: Regulatory Mechanisms Of Circrnas In Tnbcmentioning
confidence: 99%
“…Majority circRNAs identified in TNBC are characterized by oncogenic features. Specifically, circRPPH1 , circSEPT9 , circGNB1 , circPGAP3 , circUBE2D2 , circRAD18 , circAGFG1 , circKIF4A , circPLK1 , circUBAP2 , circEPSTI1 , and circGFRA1 were upregulated in both TNBC cells and tissues, and high expression of these circRNAs was able to promote tumor cell proliferation both in vitro and in vivo, and was associated with larger tumor sizes and shorter survival times for TNBC patients [ 29 , 46 , 49 , 51 , 53 , 54 , 57 , 59 , 60 , 63 , 64 , 78 ]. Similarly, circZEB1 , circEIF3M , circHER2 , hsa_circ_0131242 , hsa_circ_0005320 , hsa_circ_069718 , hsa_circ_0058514 , and circTFCP2L1 were overexpressed in TNBC cells and tissues, and they appeared to promote cell proliferation and tumor growth of TNBC [ 55 , 58 , 62 , 75 , 79 – 82 ].…”
Section: Role Of Circrnas On the Biological Functions Of Tnbcmentioning
confidence: 99%
See 2 more Smart Citations